Severe deformans tophaceous gouty arthritis (2017)
A 61-year-old man with a 20-year history of gout with severe functional disability was evaluated in our service. He received alopurinol and colchicine without response. Physical examination revealed bilateral great deformity, multiple tophi and edema of hands (Fig. 1), feet and knees. Serum uric acid was elevated: 11.2 mg/dL (reference value: 3.4–7.0 mg/dL). Hands X-ray AP view demonstrated, in both hands (Fig. 2A [left] and B [right]), conserved bone mineralization with severe soft-tissue swelling, extensive erosions with sclerotic borders (white arrows), precipitation of calcium with urate crystals giving density to the tophi (head arrows), bone spiculations (black arrows) and osteolytic expansive lesions in multiple heads of metacarpophalangic joint (double-head arrows).